Mapping of the thermodynamic performance of the supercritical CO2 cycle and optimisation for a small modular reactor and a sodium-cooled fast reactor. (1st July 2015) - Pham, H.S.; Alpy, N.; Ferrasse, J.H.; Boutin, O.; Quenaut, J.; Tothill, M.; Haubensack, D.; Saez, M.
Abstract: The supercritical CO2 (sc-CO2 ) cycle is being promoted worldwide by many R&D energy organisations and companies as an alternative to the Rankine steam cycle for its capacity to deliver high performance, simple and compact power conversion systems. The past decade has seen an extensive number of published studies carried out in view of analysing the advantages of this cycle for various applications, from nuclear to solar energies. In that context, this work first reports a mapping of the thermodynamic performance of different sc-CO2 cycle configurations that encompass a 250–850 °C TIT (turbine inlet temperature) range. The main compressor inlet temperature was chosen to be 35 °C to accommodate various heat-sink temperatures while the maximum pressure was parameterised at 20 MPa and at 25 MPa. These charts are seen to provide a preliminary engineering guideline to the maximum performance that one can expect from a sc-CO2 cycle coupled to a specific application. Additionally, they illustrate the effect of the interlinked constraints in terms of optimal recuperation power and IHX (Intermediate Heat eXchanger) inlet temperature. Following this generic study, two typical nuclear applications have been investigated with the support of an exergy analysis. A SMR (small modular reactor) featuring a current generation Pressurized Water Reactor has been chosen as an example of a low temperature range case. Parametric studies of a recompression cycle featuring a TIT of 275 °C have guided investigations regarding optimal operating conditions depending on a balance between cycle efficiency, recuperation power, and main compressor operation margin with respect to the critical point. Options for performance improvement such as reheat and condensing mode operation have been investigated for a maximum cycle pressure of 20 MPa. Thermal efficiencies of 29.3% and 28.6% respectively are reported for these two cases. This is in contrast to 27.1% for the initial recompression cycle design. Even though the penalty when compared to a Rankine steam cycle is significant, the sc-CO2 cycle in condensing mode is viewed as an interesting option thanks to its system simplicity and footprint saving. Moving to a higher temperature range, the sc-CO2 cycle has been studied at a TIT of 515 °C for a test case application to a SFR (sodium-cooled fast reactor). The recompression cycle operating at a compressor inlet temperature of 35 °C provides a maximum efficiency of 43.9% and features an optimal IHX inlet temperature of 347.8 °C. However the considered application requires that this temperature should be kept below 330 °C. Work has been carried out to optimise the cycle with regard to this specific constraint through several options including the modification of the operating conditions and the investigation of other cycle configurations. The recompression cycle in condensing mode is finally identified as the most interesting one since it achieves an efficiency of 45.7% and features an optimal IHX inlet temperature of 328.6 °C. Highlights: Thermodynamic performance of the supercritical CO2 cycle is mapped in a 250–850 °C TIT (turbine inlet temperature) range. Parametric study and optimisation are performed for a SMR (small modular reactor) and a SFR (sodium-cooled fast reactor). Cycle operation in condensing mode is found as the most promising option for both cases. Coupling to the SMR at a TIT of 275 °C provides a 28.6% thermal efficiency but allows for footprint saving. Coupling to the SFR at a TIT of 515 °C provides an attractive 45.7% thermal efficiency.